2011
DOI: 10.1186/1471-2474-12-195
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hylan G-F 20 supplementation on cartilage preservation detected by magnetic resonance imaging in osteoarthritis of the knee: a two-year single-blind clinical trial

Abstract: BackgroundAlthough viscosupplementation is an effective symptomatic treatment for knee osteoarthritis (OA), the effect of longer term administration on articular cartilage has not been fully explored. We examined the effect of viscosupplementation with Hylan G-F 20 on knee cartilage over 2 years in patients with knee OA.MethodsIn this prospective, single-blind, parallel control group pilot study, 78 patients with symptomatic knee OA (Kellgren-Lawrence grade II and III) were assigned to either intervention grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
63
0
11

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(77 citation statements)
references
References 50 publications
2
63
0
11
Order By: Relevance
“…In a magnetic resonance imaging-based RCT on articular cartilage volume change after four courses of hylan G-F 20 injection at 6-month intervals, the authors claimed that there was less cartilage loss in the treatment group at 24 months (2.7% over the medial tibial plateau and 2.6% over the lateral tibial plateau). 20 Whether these differences are clinically significant is doubtful, however. We could not find any specific factors predicting good clinical response in our patients.…”
mentioning
confidence: 99%
“…In a magnetic resonance imaging-based RCT on articular cartilage volume change after four courses of hylan G-F 20 injection at 6-month intervals, the authors claimed that there was less cartilage loss in the treatment group at 24 months (2.7% over the medial tibial plateau and 2.6% over the lateral tibial plateau). 20 Whether these differences are clinically significant is doubtful, however. We could not find any specific factors predicting good clinical response in our patients.…”
mentioning
confidence: 99%
“…high-weight molecules contribute to form a high-viscosity solution, which serves as a lubricant and shock absorber [2,25], among other functions. Viscosupplementation reportedly relieves pain [13] but it also is considered a disease-modifying OA drug [14,29] with benefits that have been observed in a period of 6 months to 2 years [22]. It is believed that the long-term effectiveness of HA is attributable to its modulating action in the inflammatory process that occurs in the osteoarthritic joint and in its interaction with the CD44 synoviocytes receptors [28,30].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials [8,29] and meta-analyses [3,7,11] have documented improvement in pain and function with viscosupplementation. Several placebo-controlled studies [4,7,11] showed an improvement began only within 2 to 5 weeks after the procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Так, Y. Wang и соавт. [35] наблю-дали 78 больных ОА коленных суставов: 39 из них получили 4 курса по 3 инъекции гилана G-F 20, 39 больных контроль-ной группы -стандартную терапию. Магнитно-резонансная томография коленных суставов выполнялась исходно, через 12 и 24 мес.…”
unclassified